Bioequivalence Study of 2 Orodispersible Formulations of Ondansetron 8 mg in Healthy Volunteers - Cánovas, M.; Rios, J.; Domenech, G.; Cebrecos, J.; Pelagio, P.; Canals, M.; Polonio, F.; Cabré, F. (Arzneimittelforschung, 2012)
This study was designed to compare the rate and extent of absorption of 2 oral formulations of ondansetron (CAS 99614-02-5) 8 mg orodispersible tablets in healthy volunteers. 22 subjects were administered ondansetron orodispersible tablets of test and reference formulation in a single-dose, 2-period, 2-sequence, fasting, open-label, crossover and randomised study. Plasma concentrations were determined by LC/MS/MS. Log-transformed AUCs and Cmax values were tested for bioequivalence based on the ratios of the geometric means (test/reference). Tmax was analysed nonparametrically. The 90% confidence intervals of the geometric mean values for the test/reference ratios for AUC0–t and Cmax were within the bioequivalence acceptance range of 80–125%. According to the European Guideline [1] it may be therefore concluded that test formulation of ondansetron 8 mg orodispersible tablet is bioequivalent to the reference formulation.
Keywords: antiemetic; bioequivalence; CAS 99614-02-5; ondansetron; pharmacokinetics